(untitled) (Научни трудове на УНСС, 2023)
The paper aims to present an overview of the publications and research activity in English for specific purposes of the faculty of the Department of Foreign Languages and Applied Linguistics at UNWE for the period 2020-2022. The department has a long-standing tradition in teaching foreign languages and a team of professionals. However, it was more focused on its teaching activity rather than on research. Recently, a change has occurred and resulted in strenuous scientific work involving a great part of the English lecturers and leading to detailed studies and surveys that are expected to improve the academic ESP course results along with the intensive efforts to design materials tailored to the needs of the UNWE students.